An examination of the perceived value of organic dining. Issue 8 (9th August 2018) - Lu, Lu; Chi, Christina Geng-qing
Abstract : Purpose: This paper aims to explore the perceived hedonic and utilitarian value of organic dining along with its antecedents and dining outcomes. Design/methodology/approach: Data were collected from two groups of US consumers who had recently visited a quick-service or upscale restaurant to consume organic menu items. Data were analyzed using factor analysis and hierarchical regression analyses using Hayes' PROCESS procedure. Findings: Perceived hedonic value has two dimensions (dining-centered excitement and social attention and escapism), as does utilitarian value (tangible value and intangible value). Involvement with organic food is a significant antecedent of perceived value. Satisfaction exhibits various mediating effects on behavioral intention, depending on the value factor considered. Research limitations/implications: This study contributes to knowledge regarding the perceived dining value of consuming organic food at restaurants. Findings shed light on the importance of understanding perceived value in predicting diners' behavioral intentions across two restaurant segments. Consumers' value perceptions of organic dining differ from those related to general organic food shopping. Practical implications: The findings provide clear ways for restaurants to increase the perceived utilitarian and hedonic value of organic food dishes. This study assists restaurant practitioners in managing customer satisfaction and loyalty by prioritizing the effort invested in developing different value perceptions. Originality/value: This research is one of the first attempts to delve into consumers' dining experiences with organic food across two major restaurant segments.